2007
DOI: 10.1016/j.jalz.2007.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Subjective memory complaints, education, and risk of Alzheimer's disease

Abstract: Especially in persons with a high level of education who still perform well on formal cognitive tests, subjective memory complaints might be an important first sign of imminent Alzheimer's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
163
2
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(181 citation statements)
references
References 13 publications
9
163
2
7
Order By: Relevance
“…Apesar de os resultados atuais não sugerirem relação entre escolaridade e queixas cognitivas, é possível que ela exista de forma modesta, sendo detectável apenas por meio de estudos longitudinais, com amostras maiores. Em análise realizada no estudo de Rotterdam 14 , por exemplo, concluiu-se que o risco para desenvolvimento da doença de Alzheimer era maior em pessoas com queixas subjetivas de memória quando elas apresentavam escolaridade elevada, e, entre estas, nas que obtêm bom desempenho em testes cognitivos formais, a queixa de memória pode ser o primeiro sinal da doença de Alzheimer. A queixa de memória era menos preditiva de doença de Alzheimer entre pessoas de baixa escolaridade.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Apesar de os resultados atuais não sugerirem relação entre escolaridade e queixas cognitivas, é possível que ela exista de forma modesta, sendo detectável apenas por meio de estudos longitudinais, com amostras maiores. Em análise realizada no estudo de Rotterdam 14 , por exemplo, concluiu-se que o risco para desenvolvimento da doença de Alzheimer era maior em pessoas com queixas subjetivas de memória quando elas apresentavam escolaridade elevada, e, entre estas, nas que obtêm bom desempenho em testes cognitivos formais, a queixa de memória pode ser o primeiro sinal da doença de Alzheimer. A queixa de memória era menos preditiva de doença de Alzheimer entre pessoas de baixa escolaridade.…”
Section: Discussionunclassified
“…Os autores destacam, ainda, a possibilidade de as queixas serem fator preditivo para a demência em indivíduos com alta escolaridade, mesmo quando não são identificados prejuízos cognitivos em avaliações breves. Estudo longitudinal recente 14 destacou a importância da queixa de memória entre idosos altamente escolarizados para a detecção precoce do declínio cognitivo.…”
Section: Introductionunclassified
“…Earlier research has shown that among people with higher education these complaints might be an important indicator of impending Alzheimer's disease (AD) [17][18][19][20][21] . In a nine-year longitudinal study, Van Oijen et al 17 demonstrated that among seniors with higher educational levels, even when they achieved normal results on cognitive tests, complaints were predictive of AD. Clinical studies have also suggested that complaints could be of better predictive value for dementia among highly educated individuals, even when no cognitive impairment is observed in brief tests 18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…Subjective cognitive decline (SCD) is actually considered to be associated with an increased likelihood of future cognitive impairment and dementia, especially among those who worry about their memory [1][2][3]. According to the suggestions made by the Working Group of the Subjective Cognitive Decline Initiative (SCD-I) [4], SCD is defined as personal complaints about one´s cognitive state in the absence of objective cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%